PENYULUHAN KESEHATAN PADA REMAJA PUTRI TENTANG PEMERIKSAAN PAYUDARA SENDIRI DI STIKES PELITA ILMU DEPOK 2022 - Wijaya, Putri - (Jurnal Abdi Mahosada, 2023)
The prevalence of cancer in Indonesia is quite high. Based on Basic Health Research (Riskesdas) data in 2013, the prevalence of tumors/cancer in Indonesia is 1.4 per 1000 population. The incidence of breast cancer is 40 per 100,000 women while cervical cancer is 17 per 100,000 women. One of the right efforts in carrying out early detection of abnormalities in the breast, especially breast cancer, is to carry out breast self-examination (BSE). The purpose of this community service activity is to provide health education to adolescents at STIKES Pelita Ilmu Depok. Methodology The population is 88 respondents. The sample technique uses total sampling. Data analysis used paired samples t test and independent t-test. The results showed that the average knowledge of adolescents before health counseling in the experimental group was 14.48 and the control was 15.32, after health counseling in the experimental group was 20.25 and the control was 15.73, the statistical test results obtained a p-value of 0.000. These results indicate that it is important to provide health education to increase knowledge about breast examination itself. It is hoped that health workers will increase counseling that can be carried out at schools and in clinics so that adolescents have knowledge and understanding of breast self-examination (BSE). Keywords: Breast Cancer, Adolescents, BSE.